2005
DOI: 10.1097/01.aco.0000182564.25057.fa
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative pain, nausea and vomiting in neurosurgical patients

Abstract: There is still a lot of scope to research and refine pain and postoperative nausea and vomiting management in cranial and spinal neurosurgical patients. Large-scale studies are required to define the current state of practice, determine effective treatments and define the incidence of side-effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 58 publications
0
20
0
1
Order By: Relevance
“…The view that craniotomy is almost never associated with postoperative pain because the brain tissue has no pain perception per se, seems very common. [3][4][5][6][7][8] However, neither did these studies change awareness of the problem nor did they result in any treatment recommendations. Similarly, pain-induced arterial hypertension increases the risk of secondary intracranial hemorrhage.…”
mentioning
confidence: 99%
“…The view that craniotomy is almost never associated with postoperative pain because the brain tissue has no pain perception per se, seems very common. [3][4][5][6][7][8] However, neither did these studies change awareness of the problem nor did they result in any treatment recommendations. Similarly, pain-induced arterial hypertension increases the risk of secondary intracranial hemorrhage.…”
mentioning
confidence: 99%
“…Opioidlerin en önemli yan etkilerinden biri de bulantı-kusmadır ve kullanılan ilaç dozuna, miktarına bağlı olarak görülme sıklığı artmaktadır. 23 Çalışmamızda toplam morfin tüke-timi açısından gruplar arasında belirgin bir fark olmadığı için de postoperatif bulantı-kusma oranlarının benzer ve dolayısıyla bu ikisinin birbirleriyle ilişkili olduğu düşünülmektedir.…”
Section: Discussionunclassified
“…In addition, longer duration of observation for PONV lasting 48 h could also be responsible for the relatively higher incidence of PONV in this study compared to that of previous studies in which patients were mostly observed only for 24 h postoperatively. And total IV anesthesia with propofol or neuraxial analgesia also may be helpful in lowering the incidence of relatively high rates of PONV [7,28]. …”
Section: Discussionmentioning
confidence: 99%
“…PONV is a significant problem for neurosurgical patients affecting patient outcome which mandates therapies aimed at active prevention. Thus, recommendations for the treatment of established PONV based on trials in neurosurgical patients may be flawed [7]. …”
Section: Introductionmentioning
confidence: 99%